Complementos direccionales en el marco predicativo de venio - Cabrillana Leal, Concepción (1997)
This paper analyses the alternative ways for expressing Direction (?) in dependence of a verb of movement: uenio. The analysis of its predicative frame concludes an association of phenomena in the different semantic and syntactic combinatorial possibilities of the predicate. From the data of the corpus chosen and the selection restrictions imposed on the terms which can be inserted into the argument positions, the author puts forward one exclusive predicative frame for uenio, and propounds different semantic relations for complements expressed in Accusative or Dative case.
Keywords: Lingüística; Lengua latina